HUBUNGAN PENGETAHUAN IBU TENTANG KESEHATAN REPRODUKSI REMAJA DENGAN UPAYA MEMPERSIAPKAN MASA PUBERTAS PADA ANAKNYA DI WILAYAH KERJA PUSKESMAS TUMPAAN - Lalogiroth, Fineke; Sri Purwanti, Anik (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Background: Puberty is a crucial phase in a child's development that requires good guidance and understanding from parents, especially mothers. Mothers' knowledge about adolescent reproductive health is very important to prepare their children to face physical and psychological changes during puberty. Objective: This study aims to analyze the relationship between mothers' knowledge about adolescent reproductive health and efforts to prepare their children for puberty in the Tumpaan Community Health Center working area. Method: This study used a cross-sectional design with a sample of 18 mothers of teenage children. Data was collected through a questionnaire that assessed mothers' knowledge about adolescent reproductive health and the efforts made to prepare their children for puberty. Data analysis was carried out using the Chi-Square test to determine the relationship between the two variables. Results: The results of the study show that the majority of mothers who have high knowledge about adolescent reproductive health tend to make better efforts to prepare their children for puberty. Of the 18 samples, mothers with good knowledge about adolescent reproductive health had higher scores for efforts to prepare for puberty compared to mothers who had low knowledge. Conclusion: There is a significant relationship between mothers' knowledge about adolescent reproductive health and efforts to prepare their children for puberty in the Tumpaan Community Health Center working area. Increasing mothers' knowledge regarding adolescent reproductive health through education